PROFIL BERPIKIR VISUAL MAHASISWA CALON GURU MATEMATIKA DALAM MEMAHAMI DEFINISI FORMAL BARISAN KONVERGEN BERDASARKAN PERBEDAAN GENDER - Darmadi Darmadi (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
The aim of this study was to get profile of visual thinking of prospective teachers of mathematics in understanding formal definitions of convergent sequences based on gender differences. This study focused more on the process than the results. The results of the study are presented in the form of descriptions based on empirical data. Therefore, it used descriptive-exploratory study with a qualitative approach. To get the depth of the data, it selected one male subject and one female subject. Method of task-based interviews with semi-structured format was used to collect the data. The time triangulation is used to validate the data. Reduction, categorization, synthesis, and inferences are used to analyze the data. The results showed that: 1) The male student does four stages or activities to understand the formal definition of convergent sequences, that is: to recognize, to imagine, to show, and to conclude.The activity to show can be categorized into two sub-activities; namely: to show a picture of convergent sequences and to show a picture attribute of the definition. The sequence of activities to understand was carried out by the male student in not a linear fashion. Profile of visual thinking of male prospective teacher of mathematics in understanding formal definitions of convergent sequences is obtained from on the information processing activities that involve mental imagery. Mental imagery processing is done through three stages, namely: to construct mental imagery, to processing mental imagery, and to utilize mental imagery. The stages of processing mental imagery can be categorized into two sub-stages; namely: to determine mental imagery and to refine mental imagery. 2) The female student does four stages or activities to understand the formal definition of convergent sequences, namely: to recognize, to imagine, to show, and to conclude. The activity to show can be categorized into two sub-activities; namely: to show a picture of convergent sequence and to show a picture attribute of the definition. To understand the sequence of activities was performed by female student in a linear fashion. Profile of visual thinking of female prospective teacher of mathematics in understandingformal definitions of convergent sequences is obtained from the information processing activities that involve mental imagery. Mental imagery processing is done through three stages namely: to construct mental imagery, to processing mental imagery, and to utilize mental imagery. The stages of processingmental imagery can be categorized into two sub-stages; namely: to determine mental imagery and to refine mental imagery. 3) Regardless of the differences in the representation and processing sequence as well as the activities and the use of mental imagery, there are similarities in the understanding of theformal definition of convergent sequences. To understand the formal definition of convergent sequences, students do four phases of activities, namely: to recognize, to imagine, to show, and to conclude. The activity to show can be categorized into two sub-activities; namely: to show a picture of convergent sequences and to show a picture attribute of the definition. Mental imagery processing is done through three stages, namely: to construct mental imagery, to processing mental imagery, and to utilize mental imagery.